Development of Apparatus Resources at the Makassar City Investment and One-Stop Service Office - Muhammad Luthfi Siraj; Aslinda Aslinda; Muh. Ikramullah Akmal; Didin Halim (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
The development of apparatus resources is an activity that must be carried out by organizations so that their knowledge, abilities, skills are in accordance with the demands of the work they are doing. This study aims to determine the development of Apparatus Resources at the Makassar City Investment and One-Stop Service Office (DPMPTSP) in terms of education and training aspects. By using descriptive quantitative research methods. Collecting data using observation, questionnaires, interviews and documentation. With data analysis technique that is descriptive analysis. The results showed that the development of apparatus in the Makassar City DPMPTSP was seen from the educational aspect which was carried out well because there was an increase in the number of employees who were given the opportunity and permission to continue their education to a higher level, such as employees who were still in high school status were prioritized to be upgraded to graduate degrees. Meanwhile, in the aspect of training, the implementation was considered quite good, where the participation of employees in training in the form of training, induction or orientation, and apprenticeships were carried out alternately every year and were carried out quite proportionally according to the type of training attended by local employees and budget availability. Overall the development of apparatus resources carried out by DPMPTSP Makassar City has been carried out well, with efforts to develop apparatus, of course it provides an increase in the knowledge and skills of employees regarding their duties and functions so that employees can work better and more productively in providing services to the community.